Perubahan Regulasi Pengelolaan Keuangan BUMN Menurut Undang-Undang No 1 Tahun 2025 tentang Badan Usaha Milik Negara: Tinjauan Filosofi Hukum - Rasji; Yuniati; Zayyan Syafiqah Aggistri (Jurnal Hukum Lex Generalis, 2024)
State-Owned Enterprises (SOEs) in Indonesia play an important role in the economy, but face challenges in transparency and accountability after Law No. 1 of 2025. This study analyzes changes in SOE financial management from a philosophical legal perspective. The results show that the elimination of the phrase "SOE capital comes from separated state assets" obscures the legal status of SOE assets and has the potential to create legal uncertainty. In addition, the provision that SOE managers are not state administrators can reduce transparency, accountability, and open loopholes for abuse of authority, as well as create the risk of uncertainty in the application of the law, especially within the framework of eradicating corruption.